2020
DOI: 10.1039/c9ra10318j
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic effect in water treatment with mesoporous TiO2/BDD hybrid electrode

Abstract: A mesoporous TiO2/BDD hybrid electrode showed a synergetic effect between electrochemical water treatment and photocatalytic water treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In our previous study, we demonstrated that oxidation ability was enhanced by using electrochemical treatment together with photocatalysis because electrochemically formed H 2 O 2 was reduced by electrons in the conduction band of TiO 2 to form OH . 5 The observed promotion of NO 2 À oxidation suggests that the photocatalyst also enhanced OH production in this study. Although the concentration of NO 3 À formed decreased (Fig.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…In our previous study, we demonstrated that oxidation ability was enhanced by using electrochemical treatment together with photocatalysis because electrochemically formed H 2 O 2 was reduced by electrons in the conduction band of TiO 2 to form OH . 5 The observed promotion of NO 2 À oxidation suggests that the photocatalyst also enhanced OH production in this study. Although the concentration of NO 3 À formed decreased (Fig.…”
supporting
confidence: 50%
“…Experiments were conducted with an H-type cell consisting of two glass cells, as described in our previous study. 5 One half cell contained the BDD working electrode and the other contained a Pt counter electrode. When the TiO 2 photocatalyst was used together with the BDD electrode, a Kr-Br excimer lamp producing 207 nm UV light (ORC Manufacturing Co., Ltd (Machida, Tokyo, Japan)) and mesoporous TiO 2 /BDD photocatalyst were included in the system.…”
mentioning
confidence: 99%
“…The configuration of p-BDD and n-metal oxide has been most widely studied. In contrast to a continuous uniform film [ 26 , 27 , 32 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], the 1D nanostructure (e.g., NRs, NWs and NTs) that is free of defects, quantum-enhanced and has a large surface-area-to-volume ratio will not encounter the thermal mismatch with diamond, thereby substantially improving the performance of the hybrid structural heterojunction. For simplicity, we will focus on three different 1D n-type metal oxide (ZnO, TiO 2 and WO 3 )/p-BDD heterojunction structure types in this review in the following general examples.…”
Section: Diamond-based 1d Metal Oxide Heterojunction Classesmentioning
confidence: 99%
“…They also used this hybrid electrode in water electrolysis to produce O 3 gas and other reactive oxygen species (ROS). In addition, ROS produced by electrochemistry were tested in water treatment under UV illumination and demonstrated the system’s suitability for advanced oxidation processes [ 27 ]. This simple water treatment system can be used to break down refractory organic matter in wastewater, a process that is still being studied.…”
Section: Diamond-based 1d Metal Oxide Heterojunction Classesmentioning
confidence: 99%
See 1 more Smart Citation